(untitled) (Bangladesh Journal of Botany, 2008)
A defensin gene isolated from chickpea (Cicer arietinum L.), Ca-AFP in the background of pCAMBIA1301 was transferred into tobacco (Nicotiana tabaccum L. var. petit havana) genome following transformation using Agrobacterium tumefaciens strain LBA4404. Although all the explants showed GUS activity after co-cultivation, transgenic tobacco shoots were regenerated only from those explants cultured in presence of bacteriostatic antibiotic carbenicillin under hygromycin selection. Presence of the antifungal gene in the regenerated plants was confirmed by PCR, while integration of the whole T-DNA was demonstrated by southern blot hybridization. Furthermore, southern blot hybridization revealed that most of the transgenics contained single copy of the T-DNA while few were found to have multiple copies. Expression of the GUS and Ca-AFP genes in the transgenic plants was observed. Morphological analysis demonstrated that presence of the transgenes produced no morphological abnormality or yield discrepancy in the transgenics. Â Key words: Ca-AFP, Tobacco, Chickpea, Defensin peptide, Bacteriostatic antibiotics doi:10.3329/bjb.v36i1.1548 Bangladesh J. Bot. 36(1): 47-52, 2007 (June)